The Tyranny of Language in Education : The Problem and its Solution - Zubeida Mustafa (Oxford Oxford University Press, 2015)
Language is central to a person's development in society. It is also a key factor in education. In this book, the author looks at the education from the perspective of educating young children, which has so far not been done in Pakistan. This book should show the way forward.
Include Index and Bibliography
Keywords: Pakistan -- Language and education -- Language policy